The Effect of Respiratory Muscle Stretch Gymnastic (RMSG) on Lung Capacity in The Elderly - Nugraharani, Dorotea Galuh Puspita; Amarseto, Binuko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The elderly are members of society who must be paid attention to, because in the elderly there will be changes, one of which is in the respiratory system, in this case lung capacity, which is influenced by aging, environmental and lifestyle factors which can be measured with a tool called spirometry. Efforts that can be made to maintain lung function in the elderly are by providing exercise, one of which is Respiratory Muscle Stretch Gymnastics (RMSG). The aim of this research was to determine RMSG on lung capacity in the elderly at the Posyandu for the Meaningful Elderly. The research method used was Quasi Experimental with a Pretest-Posttest Control Group Design research design. The sampling technique was Purposive Random Sampling and a sample of 30 elderly people were obtained which were divided into 2 groups. Data collection was carried out using spirometry, which was then carried out by univariate and bivariate analysis tests. The research results showed that there was an effect of RMSG on the elderly with the results in the intervention group increasing the average value, while in the control group the average value decreased. The conclusion obtained based on the results of data analysis is that there is an effect of giving RMSG on lung capacity in the elderly.